Understanding the behavioral intention to use SaaS ERP sub-modules considering perceived enjoyment, perceived anxiety and perceived system performance - Yap, Mun Keong *; Lee, Angela Siew Hoong * (Springer, 2020)
The use of cloud solution to support Enterprise Resource Planning (ERP) system has become the priority of many organizations to stay competitive in the current global world. This research will be focusing on the behavioral intention among the employees to use Software as a Service (SaaS) ERP sub-modules in a global construction tool provider considering perceived enjoyment, anxiety and system performance. The objective of this research is to analyze and investigate the employees’ behavioral intention to use SaaS ERP sub-modules in the construction tool provider companies considering these unique variables and predictors. The findings of this research can assist and support both organizations and researchers to build a fundamental level on understanding how these variables can predict the user behavioral intention to use SaaS ERP sub-modules in a global construction tool provider company which significantly beneficial. 250 users ranging from executive and higher management level globally were targeted in 25 countries. A statistical tool will be used to analyze respondents’ data and structural equation modelling will be used to analyses the responses and the relation of each hypothesis. The hypothesis will be tested based on the data consolidated.